Genetic variation among cocoa (Theobroma cacao L.) families for resistance to cocoa swollen shoot virus disease in relation to total phenolic content. Issue 4 (4th June 2015) - Ofori, Atta; Padi, Francis Kwame; Ameyaw, George Akumfi; Dadzie, Abu Mustapha; Lowor, Samuel; Flachowsky, H.
Abstract Phenolic compounds have been suggested as one of the defence mechanisms to cocoa swollen shoot virus disease (CSSVD), but not well studied. Correlation and genetic variation of total phenolic content (TPC) and CSSVD resistance among 53 cocoa families were investigated. Three‐month‐old seedlings of 15 families obtained from an incomplete 6 × 3 NCII mating design, of 24 families from a 3 × 8 NCII mating design and of 14 other families were evaluated for CSSVD and TPC. Plants were inoculated with viruliferous mealybugs carrying the New Juaben CSSV strain (1A) in a gauze house facility. A single seedling randomization within blocks procedure was followed, using the gauze house units as blocks. There were six blocks with five seedlings of each family randomized within each block. Disease severity scores on leaf flushes at the first, second, third and seventh flushes after inoculation were recorded. The TPC before and 3 months after inoculation was also determined. Family effects were highly significant (P ≤ 0.01) for CSSVD severity scores and TPC. Narrow‐ and broad‐sense heritability estimates were low for CSSVD severity but moderate to high for TPC evaluations. Correlations between severity scores and TPC were weak (r = −0.22 to 0.40) suggesting that the TPC may be of little value in selecting CSSVD resistance varieties in cocoa. Additive effect in terms of significant GCA was important for CSSVD severity scores whereas both additive and non‐additive effects were important for TPC values when the 3 × 8 and 6 × 3 NCII mating designs were analysed. Only clones GU 239/H, GU 290/H and GU 225/V had favourable GCA effects for CSSVD symptom expression indicating their potential for developing progeny with high levels of resistance to CSSVD infection.